Akli Mohand Walhaj, leader of the third historical department A view of his positions on the issues of the transitional period (1962) - jellaoui, saidd (The Algerian Historical Journal, 2026)
This study deals with one of the revolutionary personalities, who is Colonel Akli Mohand OualHadj, the leader of the historical third state. Far from the biographical study that stands on the narration of the man’s struggle path, we specifically address his positions and opinions on some of the complex transitional issues and their approach with the lines drawn by the texts of the liberation revolution, stating that France’s exit from Algeria after staying 132 years will leave behind a very complex general situation, especially what It is related to the political issues that were dealt with in the Evian Accords, but the reality devoted in that short period and related to the interactions of the revolution is difficult to determine on the ground. Here the colonel had a personal view of this reality.